1994
DOI: 10.1073/pnas.91.20.9612
|View full text |Cite
|
Sign up to set email alerts
|

Functional magnetic resonance studies of the reorganization of the human hand sensorimotor area after unilateral brain injury in the perinatal period.

Abstract: Functional magnetic resonance ging was used to map the hand sensorimotor area of hemiparetic adolescents and young adults who had suffered unilateral brain damage in the perinatal period. Unlike normal subjects, who exhibit cortical activation primarily contralateral to voluntary finger movements, the hemaretic patients' intact hemispheres were equally activated by contralateral and ipsilateral finger movements. Our fidings are consistent with previous clinical observations and animal experiments which suggest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
64
0
1

Year Published

1998
1998
2011
2011

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 130 publications
(70 citation statements)
references
References 36 publications
5
64
0
1
Order By: Relevance
“…After unilateral neonatal pyramidotomy in rodents, corticoefferent fibers from the same side as the lesion were found to cross the midline to form new connections with medullary nuclei and to descend to spinal cord levels . Evidence that new neural connections occur after perinatal brain damage in children is supported by several clinical studies (Farmer et al, 1991;C arr et al, 1993;C ao et al, 1994). Structural neuroplasticity is thought to play an essential role in recovery of function, because animals sustaining C NS lesions at a young age are known to recover much better than those sustaining similar lesions at maturity (Kennard, 1936(Kennard, , 1938Whishaw and Kolb, 1988;Armand and Kably, 1993).…”
mentioning
confidence: 66%
“…After unilateral neonatal pyramidotomy in rodents, corticoefferent fibers from the same side as the lesion were found to cross the midline to form new connections with medullary nuclei and to descend to spinal cord levels . Evidence that new neural connections occur after perinatal brain damage in children is supported by several clinical studies (Farmer et al, 1991;C arr et al, 1993;C ao et al, 1994). Structural neuroplasticity is thought to play an essential role in recovery of function, because animals sustaining C NS lesions at a young age are known to recover much better than those sustaining similar lesions at maturity (Kennard, 1936(Kennard, , 1938Whishaw and Kolb, 1988;Armand and Kably, 1993).…”
mentioning
confidence: 66%
“…The recovery of motor function, which indicated the complexity and interplay of neuronal activity among different motor areas, led to the study of "functional reorganization" and "plasticity" in patients with stroke, [10,46] brain injury, [8] and brain tumors. [42] Studying six patients after their recovery from hemiplegic stroke by using PET, Chollet, et al, [10] demonstrated bilateral activation (rCBF increase) of MII, SMA, and insula during movement of the recovered fingers.…”
Section: Reorganization Of Cortical Motor Cortexmentioning
confidence: 99%
“…This suggests that further mechanisms must be involved, e.g. an increased use of ipsilateral pathways that then connect to commissural systems (Cao et al, 1994;Chiarello, 1980). Furthermore, bimodal cells, which integrate information from different sensory modalities (reviewed by Stein & Stanford, 2008), are not only found in cortical structures (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…It is well-known that developmental malformations may affect cerebral functioning in several ways (Cao, Vikingstad, Huttenlocher, Towle, & Levin, 1994;Hicks & D'Amato, 1970). The crossmodal congruency task also allowed us to compare performance between AgCC patients and controls for cases in which no hemispheric transfer was necessary to test whether the absence of the corpus callosum alters information processing within one hemisphere.…”
Section: Introductionmentioning
confidence: 99%